Primary and Secondary Education During Covid-19 Disruptions to Educational Opportunity During a Pandemic - Reimers, Fernando M. (Springer International Publishing : Imprint: Springer, 2022)
This open access edited volume is a comparative effort to discern the short-term educational impact of the covid-19 pandemic on students, teachers and systems in Brazil, Chile, Finland, Japan, Mexico, Norway, Portugal, Russia, Singapore, Spain, South Africa, the United Kingdom and the United States. One of the first academic comparative studies of the educational impact of the pandemic, the book explains how the interruption of in person instruction and the variable efficacy of alternative forms of education caused learning loss and disengagement with learning, especially for disadvantaged students. Other direct and indirect impacts of the pandemic diminished the ability of families to support children and youth in their education. For students, as well as for teachers and school staff, these included the economic shocks experienced by families, in some cases leading to food insecurity and in many more causing stress and anxiety and impacting mental health. Opportunity to learn was also diminished by the shocks and trauma experienced by those with a close relative infected by the virus, and by the constrains on learning resulting from students having to learn at home, where the demands of schoolwork had to be negotiated with other family necessities, often sharing limited space. Furthermore, the prolonged stress caused by the uncertainty over the resolution of the pandemic and resulting from the knowledge that anyone could be infected and potentially lose their lives, created a traumatic context for many that undermined the necessary focus and dedication to schoolwork. These individual effects were reinforced by community effects, particularly for students and teachers living in communities where the multifaceted negative impacts resulting from the pandemic were pervasive. This is an open access book.